If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + 24 = 4m + -4 Combine like terms: -3 + 24 = 21 21 = 4m + -4 Reorder the terms: 21 = -4 + 4m Solving 21 = -4 + 4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4m' to each side of the equation. 21 + -4m = -4 + 4m + -4m Combine like terms: 4m + -4m = 0 21 + -4m = -4 + 0 21 + -4m = -4 Add '-21' to each side of the equation. 21 + -21 + -4m = -4 + -21 Combine like terms: 21 + -21 = 0 0 + -4m = -4 + -21 -4m = -4 + -21 Combine like terms: -4 + -21 = -25 -4m = -25 Divide each side by '-4'. m = 6.25 Simplifying m = 6.25
| 3lg(x+2)=9 | | -3y+3(2y+6)=2-6(3-y) | | 4k(7k-4)= | | 4+7x=6x+13 | | 7y=3bx+28 | | -8-x=-7x+28 | | 1.74=LN(x+.71) | | 1506+100.25x=225.75x | | 9+7x=5x-5 | | A=by+cox+d | | 1+4t-4t+1+4t=10 | | (e/3)=6 | | 5(w+1)-w=3(w+1)+7 | | 15x^2/3 | | Xp-qx=n | | [z-3i]+[z+3i]=10 | | -10+2x=x-2 | | -(1-5)=54 | | 1+2t-2t+1+3t=6 | | Y/-65=2 | | 5t(w+1)-w=3(w-1)+7 | | -4x+7=-15-2x | | abs(z-3i)+abs(z+3i)=10 | | 2X^4+4X^3+8X^2+8X+4=0 | | 3000+40.25x=1770+60.75x | | 7x+5=20+2x | | X+5=x+.25x | | (4/5)×=1 | | 4+3x=5x-20 | | 4/5×=1 | | 1+2t-2t+1+3t=10 | | 2x^3-4x^2-20=0 |